Strategies Used by Iraqi EFL Students To Process English Idioms - حازم حسين كمال; عبد الواحد ذنون اشرف (Al-Adab Journal, 2018)
Idioms are considered to be a type of phraseological units which are largely figurative in nature and widely used in human languages. In fact, the level of command of idioms serves as an important indicator of language proficiency. Many non-native learners of English do their best to be fluent and have a native-like proficiency; this entails, among other things, a good mastery of multiple words expressions in general and idioms in particular. Perhaps the most difficult part in learning idioms for EFL learners is learning both literal and figurative meanings of these expressions. The present research attempts to investigate the strategies used by Iraqi EFL learners of English to identify the meaning of unfamiliar idioms. To achieve the aim of the present research, it is hypothesized that there is no statistically significant difference among EFL university students as far as the guessing strategies are concerned. To examine the validity of this hypothesis, a sample was chosen from the second–year students at the Department of English (College of Education for Humanities / University of Mosul) during the academic year 2012-2013. The sample consisted of 39 students. Since the present research requires preparation of two tools, the researchers designed an idiom familiarity questionnaire and a questionnaire to identify the strategies used by the subjects to infer the meaning of idioms. The results reveal that there is statistically significant difference among EFL university students as far as the guessing strategies are concerned.